2022
DOI: 10.3390/ani12182381
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Enzyme and Probiotics on the Growth Performance and Nutrient Digestibility of Broilers Fed with a Newly Harvested Corn Diet

Abstract: A new grain phenomenon happens in newly harvested corn because of its high content of anti-nutritional factors (ANFs), which can cause low nutrient digestibility and diarrhea in animals. Enzymes and probiotics have been shown to relieve the negative effect of ANFs for animals. The purpose of this study was to investigate the effect of enzymes and probiotics on the performance and nutrient digestibility of broilers, fed with newly harvested corn diets. A total of 624 Arbor Acres Plus male broiler chickens were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Improvements in intestinal morphological characteristics demonstrate enhanced digestibility and absorption of nutrients in broilers, which may improve their FCR and ultimately lead to improved growth performance. In the early stage of this study, it was indeed observed that the supplementation of BCC had a tendency to decrease the feed conversion rate of broilers, but had no effect on growth performance ( Luo et al, 2022 ). However, the mechanism of action of enzymes and probiotics to improve intestinal morphology is still not clear.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Improvements in intestinal morphological characteristics demonstrate enhanced digestibility and absorption of nutrients in broilers, which may improve their FCR and ultimately lead to improved growth performance. In the early stage of this study, it was indeed observed that the supplementation of BCC had a tendency to decrease the feed conversion rate of broilers, but had no effect on growth performance ( Luo et al, 2022 ). However, the mechanism of action of enzymes and probiotics to improve intestinal morphology is still not clear.…”
Section: Discussionmentioning
confidence: 75%
“…It was shown that xylanase and probiotics can improve the intestinal barrier function of broiler chickens and maintain intestinal homeostasis by up-regulating the mRNA expressions of MUC2, Claudin-1, and Occludin. Additionally, our previous research found that the use of newly harvested corn to formulate poultry diets resulted in decreased starch digestibility and diarrhea in broilers ( Luo et al, 2022 ). This may be due to the high content of antinutritional factors such as total pentosans and water-soluble pentosans in newly harvested corn ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The proteases or proteinases are proteolytic enzymes that can be used to hydrolyze the trypsin inhibitor of flaxseed [5]. A study reported that protease in corn-based diets increases the chyme emptying time and trypsin activity, leading to enhanced energy absorption [15]. However, the impact of proteases on amino acid digestibility is dependent on the product, supplementation level, and diet composition [16,17].…”
Section: Introductionmentioning
confidence: 99%